Hierarchical i* Modeling in Requirement Engineering - Kridanto Surendro; Cicely Martini Asihwardji (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Requirement engineering is the earliest phases of the development process of information systems in which there is a process to understand the needs of system users and formulate it into a format that facilitates the process of analysis. Requirement engineering approach through intentional perspective is one of the arguments that appear in the field. In intentional modeling, the focus will lie on the motive of every actor, how each actor can achieve their motives, and what dependencies present in order to achieve that motive. Some existing intentional modeling still has some limitations. Modeling is still having complexity problem when it will be used to model real-world situations that are quite large. Another disadvantage is how to describe the hierarchical conditions in intentional modeling. This research is to develop existing intentional modeling, in order to overcome limitations in describing the hierarchical conditions.